Evaluating the Autonomy of the Drosophila Circadian Clock in Dissociated Neuronal Culture - Sabado, Virginie; Vienne, Ludovic; Nagoshi, Emi (Frontiers in Cellular Neuroscience, 2017)
Circadian behavioral rhythms offer an excellent model to study intricate interactions between the molecular and neuronal mechanisms of behavior. In mammals, pacemaker neurons in the suprachiasmatic nucleus (SCN) generate rhythms cell-autonomously, which are synchronized by the network interactions within the circadian circuit to drive behavioral rhythms. However, whether this principle is universal to circadian systems in animals remains unanswered. Here, we examined the autonomy of the Drosophila circadian clock by monitoring transcriptional and post-transcriptional rhythms of individual clock neurons in dispersed culture with time-lapse microscopy. Expression patterns of the transcriptional reporter show that CLOCK/CYCLE (CLK/CYC)-mediated transcription is constantly active in dissociated clock neurons. In contrast, the expression profile of the post-transcriptional reporter indicates that PERIOD (PER) protein levels fluctuate and approximately 10% of cells display rhythms in PER levels with periods in the circadian range. Nevertheless, PER and TIM are enriched in the cytoplasm and no periodic PER nuclear accumulation was observed. These results suggest that repression of CLK/CYC-mediated transcription by nuclear PER is impaired, and thus the negative feedback loop of the molecular clock is incomplete in isolated clock neurons. We further demonstrate that, by pharmacological assays using the non-amidated form of neuropeptide pigment-dispersing factor (PDF), which could be specifically secreted from larval LNvs and adult s-LNvs, downstream events of the PDF signaling are partly impaired in dissociated larval clock neurons. Although non-amidated PDF is likely to be less active than the amidated one, these results point out the possibility that alteration in PDF downstream signaling may play a role in dampening of molecular rhythms in isolated clock neurons. Taken together, our results suggest that Drosophila clocks are weak oscillators that need to be in the intact circadian circuit to generate robust 24-hr rhythms.